The Effect of Local Own-Source Revenue, General Allocation Funds, Budget Surplus/Deficit, and Capital Expenditure on Regional Loans - Destira Prawinda; Kartika Rachma Sari; Siska Aprianti (LifeSciFi, 2026)
Regional loans play an important role in supporting regional development when local fiscal resources are insufficient. However, previous studies have reported inconsistent findings regarding the fiscal factors influencing regional loans. This study investigates the effects of local own-source revenue, the general allocation fund, budget surplus/deficit, and capital expenditure on regional loans in Indonesia. A quantitative approach was employed using balanced panel data from 17 provinces during 2020–2024 (85 province-year observations). Secondary data obtained from the audited Regional Government Financial Statements were analyzed using panel data regression with the Random Effect Model (REM) in EViews 13. The results indicate that local own-source revenue, budget surplus/deficit, and capital expenditure positively and significantly affect regional loans, whereas the general allocation fund has no significant effect. Simultaneously, all variables significantly influence regional loans. These findings suggest that regional loan decisions are primarily driven by fiscal capacity, budget conditions, and investment needs, providing updated evidence to support more effective regional fiscal management. The findings also provide practical implications for policymakers in formulating sustainable regional loan strategies while strengthening fiscal capacity and supporting long-term regional development.